2009
DOI: 10.1002/stem.209
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Activity in the Developing Human Cornea

Abstract: The adult cornea harbors stem cells (SCs) in its periphery, in a niche known as the limbus. Over the past 2 decades there has been substantial research into these adult corneal SCs, their limbal niche, and their therapeutic applications. However, few studies have investigated how this niche and its SCs develop in humans. To better characterize this development, human fetal corneas from 8.5-to 22-weeks'-gestation (n 5 173), neonatal (n 5 2), and adult (n 5 10) specimens were obtained. Histological and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
8
26
0
Order By: Relevance
“…In the mammalian cornea, epithelial cells with strong proliferative capacity and stem cell-like properties are initially distributed across the entire cornea (Chung et al, 1992;Collinson et al, 2002;Davies et al, 2009). As the embryo develops, corneal stem cells become restricted to the peripheral edge of the cornea, the limbus (Davies and Di Girolamo, 2010).…”
Section: Long-term Clonal Analyses In the Corneamentioning
confidence: 99%
“…In the mammalian cornea, epithelial cells with strong proliferative capacity and stem cell-like properties are initially distributed across the entire cornea (Chung et al, 1992;Collinson et al, 2002;Davies et al, 2009). As the embryo develops, corneal stem cells become restricted to the peripheral edge of the cornea, the limbus (Davies and Di Girolamo, 2010).…”
Section: Long-term Clonal Analyses In the Corneamentioning
confidence: 99%
“…This is somewhat peculiar in evolutionary sense especially when the directly adjacent conjunctiva is maintained in the same way as any other epithelia [134] . In fetal eyes, adult LSC markers are found in the basal layer across the cornea [135,136] and it is unknown how the markers become segregated in the limbus during development. Investigation of limbal organogenesis has raised a possibility that the limbal papillary structures are mere developmental remnants.…”
Section: Developmental Origin Of Limbusmentioning
confidence: 99%
“…Investigation of limbal organogenesis has raised a possibility that the limbal papillary structures are mere developmental remnants. The limbus does not develop until eyelids open and the ocular surface is exposed to amniotic fluid [135,136] . The papillary structures of the limbus do not form until post-natal life [137] .…”
Section: Developmental Origin Of Limbusmentioning
confidence: 99%
“…Several recent studies showed that under appropriate culture conditions, ESCs can differentiate into corneal epithelial cell (CEC)-like cells, [24][25][26][27] which strongly expressed specific terminally differentiated CEC markers CK3, CK12, and Cx43/50. However, the proliferative capacity of these CEC-like cells was limited and could hardly subculture in vitro.…”
Section: Introductionmentioning
confidence: 99%